Transcript Expression Patterns Illuminate the Mechanistic Background of Hormesis in Maupas - Christian E.W. Steinberg; Kerstin Pietsch; Nadine Saul; Stefanie Menzel; Suresh C. Swain; Stephen R. Stürzenbaum; Ralph Menzel (SAGE Publishing, 2013)
The animal model Caenorhabditis elegans was employed to study polyphenol- and humic substances-induced hormetic changes in lifespan. A detailed insight into the underlying mechanism of hormesis was uncovered by applying whole genome DNA microarray experimentation over a range of quercetin (Q), tannic acid (TA), and humic substances (HuminFeed®, HF) concentrations. The transcriptional response to all exposures followed a non-linear mode which highlighted differential signaling and metabolic pathways. While low Q concentrations regulated processes improving the health of the nematodes, higher concentrations extended lifespan and modulated substantially the global transcriptional response. Over-represented transcripts were notably part of the biotransformation process: enhanced catabolism of toxic intermediates possibly contributes to the lifespan extension. The regulation of transcription, Dauer entry, and nucleosome suggests the presence of distinct exposure dependent differences in transcription and signaling pathways. TA- and HF-mediated transcript expression patterns were overall similar to each other, but changed across the concentration range indicating that their transcriptional dynamics are complex and cannot be attributed to a simple adaptive response. In contrast, Q-mediated hormesis was well aligned to fit the definition of an adaptive response. Simple molecules are more likely to induce an adaptive response than more complex molecules.